DIVERGENT APPROACHES TO POST-ACUTE CARE MANAGEMENT – A CASE FOR RELATIONAL COORDINATION. (11th November 2018) - McHugh, J; Shield, R R; Tyler, D A; Gadbois, E A; Winblad, U; Mor, V
Abstract: This research highlights contrasting care management strategies and outcome differences for patients discharged to skilled nursing facilities (SNFs) from two hospitals in one hospital market. Employing a case study methodology, we compared one hospital that approached SNF partnerships through relational coordination with a competing hospital that did not. Data from clinical and administrative staff interviews and adjusted rehospitalization rate results were compared and contrasted. Analysis of interviews from the hospital that integrated with SNFs (H1) noted they provide patients detailed information at discharge, educated SNF staff, and provided input into SNF care protocols. Staff from the hospital that did not integrate with SNFs (H2) indicated a wish to do so despite previously failed attempts to manage patients in SNF. The readmission rate for patients discharged to SNF from H1 decreased from 23.4% to 14.8% as compared with an increase from 15.6% to 16.0% in H2.